HUMANISME RELIGIUS DALAM PEMIKIRAN KI HAJAR DEWANTARA: ANALISIS RELEVANSI TERHADAP PENDIDIKAN AGAMA ISLAM KONTEMPORER - Hasnun Umar; Emelia; Masnua’atul Khoiriyah; Annisa Maryan Nurrohmah; Ahsan Hakim (JDP (JURNAL DINAMIKA PENDIDIKAN), 2025)
This study aims to analyze the concept of religious humanism in the thought of Ki Hajar Dewantara and its relevance to strengthening contemporary Islamic education. The background of this research arises from the challenges of modern education, which tend to emphasize cognitive and materialistic aspects while neglecting spiritual and moral values. This study employs a qualitative approach using the library research method. The findings reveal that Dewantara’s concept of religious humanism positions human beings as rational and faithful creatures who maintain a balance between freedom, responsibility, and spiritual awareness. Educational values such as Tut Wuri Handayani and the Tri Pusat Pendidikan (Three Centers of Education) align with Islamic educational principles that emphasize moral formation and the development of students’ innate potential (fitrah). Furthermore, the study highlights the practical implications of Dewantara’s thought in reinforcing Islamic educational paradigms to become more humanistic, contextual, and culturally rooted. Thus, Dewantara’s concept of religious humanism serves as a philosophical foundation for the development of Islamic education oriented toward the formation of insān kāmil (the complete human being).